2022
DOI: 10.1021/acsmedchemlett.2c00154
|View full text |Cite
|
Sign up to set email alerts
|

Long-Awaited Small-Molecule Drug Candidate for Drugging the Next Undruggable KRASG12D Mutant in Cancer Therapy

Abstract: Disease Area. Cancer Biological Target. KRAS G12D mutant Summary. RAS (the rat sarcoma viral oncogene homologue) encodes a membrane-bound protein; it was initially described in the 1960s by Harvey and Kirsten as a retroviral oncogene involved in cells. However, it was in 1982 that the transforming properties of RAS were reported in human bladder cancer cell lines, which is considered the most frequently mutated oncogene in humans. Notably, the KRAS (Kirsten rat sarcoma viral oncogene) isoform represents 75% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have revealed that mutated KRAS expression is associated with reduced anticancer activity of gemcitabine and paclitaxel, the drugs currently used in the clinical treatment of pancreatic cancer, and new therapeutic strategies of targeting KRAS should inhibit tumor cell growth and combat drug resistance ( Kimmelman, 2015 ; Grasso et al, 2017 ). The majority of cancer-associated hotspot mutations occur at codons G12, G13, and Q61, wherein G12 represents the most common mutation site ( Kargbo, 2022 ). Among dominant mutations at G12, G12D has the highest mutation frequency (35.4%), followed by G12V (23.5%), G12R (8.7%) and G12C (4.3%), which has aroused the interest of many drug researchers in developing new cancer treatment methods targeting KRAS G12D mutant ( Salem et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that mutated KRAS expression is associated with reduced anticancer activity of gemcitabine and paclitaxel, the drugs currently used in the clinical treatment of pancreatic cancer, and new therapeutic strategies of targeting KRAS should inhibit tumor cell growth and combat drug resistance ( Kimmelman, 2015 ; Grasso et al, 2017 ). The majority of cancer-associated hotspot mutations occur at codons G12, G13, and Q61, wherein G12 represents the most common mutation site ( Kargbo, 2022 ). Among dominant mutations at G12, G12D has the highest mutation frequency (35.4%), followed by G12V (23.5%), G12R (8.7%) and G12C (4.3%), which has aroused the interest of many drug researchers in developing new cancer treatment methods targeting KRAS G12D mutant ( Salem et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%